(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Selar fish is a potential small pelagic fishery resource in Indonesian territorial waters and is located in Maluku Province, it specially in west seram waters. This research was carried out in the waters of West Seram, Maluku, from March 2018 to February 2019. The objective of research was to study the stock condition of bigeye scad, Selar crumenophthalmus, based on population dynamic from length frequency distribution. Fish samples were collected every month at fish landing from lift net fishers. Totally, there were 1890 individuals collected during the study, excepted June, composed of 925 males and 965 females with the length size ranging from 13.3 cm to 27.2 cm which was composed of 2 and 3 cohorts every month. Condition stock of bigeye scad based on yield per recruit analysis showed that the stock was still below the level of MSY (0.03 of 0.047), obtained from L∞ was 27.40 cm, K was 1.55/yr, Z was 3.66/yr, M was 2.51/yr, F was 1.15/yr, E was 0.32/yr, Lc was 19.92 cm and t0 was -0.10 /yr. This shows that the higher Lc value of selar fish in west seram waters more selective and otherwise.